An Exploration on the Attachment, Acculturation, and Psychosocial Adjustment of Chinese International Students in Japan - Yin, Mengxi; Aoki, Kikuyo; Liao, Kelly Yu-Hsin; Xu, Hui (Journal of International Students, 2021)
In this study, we selected Chinese students (N = 277) studying in Japan as research participants to examine the relation among their attachment, acculturation, and psychosocial adjustment. The study’s first finding revealed that Chinese students studying in Japan had a better adjustment outcome than those in America in terms of sociocultural adjustment but not psychological adjustment. The second set of findings from the results of hierarchical multiple regression analyses showed that psychological distress and sociocultural adjustment could be predicted by attachment anxiety and avoidance. Third, we found a positive correlation between acculturation to the host culture and sociocultural adjustment difficulties. Fourth, we did not find a correlation between acculturation to the host culture and attachment anxiety and avoidance. We offer a discussion on the findings and limitations in light of the unique Japanese sociocultural context.